The Implementation of Educandy Game for Vocabulary Acquisition: تطبيق لعبة إيدوجاندي لإتقان المفردات - Nafisah, Durratun; Abbas, Abbas (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2025)
Vocabulary constitutes a fundamental component of language, as mastery of vocabulary enhances comprehension of both written and spoken texts. Achieving fluency in Arabic likewise depends greatly on the acquisition of an extensive vocabulary. Hence, the purpose of this study is to examine the effectiveness of employing the Educandy game in improving vocabulary mastery among first-grade students at the State Islamic Senior High School 2 of Lhokseumawe. The researcher adopted a quantitative approach through an experimental study, utilizing a quasi-experimental design with a nonequivalent control group and administering both pre-tests and post-tests. The research population comprised all first-grade students of the school (87 students), while the sample consisted of 59 students. Results of the Mann–Whitney test yielded a significance value of 0.000, which is lower than the threshold of 0.05, indicating rejection of the null hypothesis and acceptance of the alternative hypothesis. Furthermore, the N-Gain score for the experimental group reached 62%, reflecting a moderately effective category. Accordingly, the findings of this study suggest that the application of the Educandy game is effective in enhancing vocabulary mastery among first-grade students at the State Islamic Senior High School 2 of Lhokseumawe.